2017
DOI: 10.1590/0103-8478cr20161110
|View full text |Cite
|
Sign up to set email alerts
|

Use of metaphylactic protocols based on the risk to develop bovine respiratory diseases in feedlot cattle

Abstract: Bovine respiratory diseases (BRD) affect production rates negatively because it compromise health and well-being of the affected animal. The hypothesis of this study was that the use of metaphylactic protocols based on the risk to develop BRD would reduce morbidity and pulmonary lesions. For this purpose, the aims of this study were to evaluate the effect of two metaphylactic protocols on the morbidity of feedlot cattle with a known sanitary history, occurrence of pulmonary lesions at slaughter, and the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In Brazil, information relative to the occurrence of BRD is limited when compared with studies from North America (25)(26)(27)(28) and Australia (29,30). Previous studies done in Brazil were designed to investigate a single (31)(32)(33)(34)(35)(36)(37) or several agents (2,16,(38)(39)(40)(41)(42)(43) associated with BRD. These studies focused on the molecular identification of agents, with and without the histopathologic diagnosis of the patterns of pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, information relative to the occurrence of BRD is limited when compared with studies from North America (25)(26)(27)(28) and Australia (29,30). Previous studies done in Brazil were designed to investigate a single (31)(32)(33)(34)(35)(36)(37) or several agents (2,16,(38)(39)(40)(41)(42)(43) associated with BRD. These studies focused on the molecular identification of agents, with and without the histopathologic diagnosis of the patterns of pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies done in Brazil have demonstrated concomitant action of respiratory agents of BRD (Baptista et al, 2017;Beuttemmuller et al, 2017;Magalhães et al, 2017;Tortorelli et al, 2017;Gaeta, Ribeiro, Alemán, Yoshihara, & Nassar, 2018;Oliveira & Pelaquim, et al 2020;Oliveira & Dall Agnol, et al 2020) using molecular identification with or without histopathological and immunohistochemical diagnoses. This trend of concomitant infections in BRD is evident in other countries such as in the USA (Fulton et al, 2009;Schneider, Tait, Busby, & Reecy, 2009;Taylor et al, 2010), Canada (Gagea et al, 2006;Booker, Abutarbush, Morley, Jim, & Pittman, 2008;Jim, 2009), and Australia (Cusack, McMeniman, & Lean, 2003;Moore et al, 2015;Hay et al, 2016).…”
Section: Bacterialmentioning
confidence: 99%
“…The affected cattle suffer the effects of individual disease agents or more often by a combination of several pathogens (Fulton & Confer, 2012), so clinical evaluations must include the examination of several animals of the same farm (Caswell, Hewson, Slavić, DeLay, & Bateman, 2012). The DART system that evaluates the clinical signs (depression, appetite, respiratory, temperature) of pulmonary disease, is recommended for the clinical evaluation of animals with BRD (Wilson, Step, Maxwell, Wagner, & Richards, 2015), and has been used in several studies by our group Magalhães et al, 2017). However, the isolated use of clinical manifestations is not the best method to diagnose BRD (Fulton & Confer, 2012).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations